(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: Human immunodeficiency virus (HIV), the primary cause of Acquired Immunodeficiency Syndrome (AIDS), is responsible for millions of deaths worldwide. As of 2022, Nigeria has a prevalence rate of 1.4%, with approximately 1.9 million individuals infected, contributing to about two-thirds of the deaths attributable to this illness in sub-Saharan Africa. Micronutrient deficiency is a common issue among individuals living with HIV, exacerbating immune suppression, negatively impacting prognosis, and accelerating the progression of the infection. Therefore, this research aimed to investigate the effects of various doses of selenium and zinc supplements on the weight and immune function of HIV-infected individuals through weight and CD4 monitoring, with the goal of providing a solution for improved management of HIV. A total of 30 subjects (25 HIV-infected individuals and 5 healthy controls) were selected and divided into six groups, with five individuals per group; groups 1 and 6 served as negative and positive controls, respectively. Different doses of selenium and zinc, or combinations thereof, were administered to the groups for 12 weeks while assessing the outcomes through weight measurements and CD4 count analysis at 28-day intervals. The generated data were analyzed using two-way ANOVA. The results demonstrated a significant difference in mean weight and CD4 counts across the different groups (p-value < 0.05). This indicates that selenium and zinc supplements are viable options for enhancing antiretroviral therapy (ART) in the treatment of HIV..